2007
DOI: 10.1143/ptps.168.194
|View full text |Cite
|
Sign up to set email alerts
|

Axial Vector Tetraquark with Twos-Quarks

Abstract: Possibility of an axial vector isoscalar tetraquark udss is discussed. If a f 1 meson in the mass region 1.4 − 1.5 GeV consists of four quarks nsns, the mass of the isoscalar udss(ϑ +meson) state with J P = 1 + is expected to be lower than that of the f 1 meson. Within a flux-tube quark model, a possible resonant state of udss(J P = 1 + ) is suggested to appear at ∼ 1.4 GeV with the width O(20 ∼ 50) MeV. We propose that the ϑ + -meson is the good candidate for the tetraquark search, which would be observed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
182
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(193 citation statements)
references
References 17 publications
9
182
2
Order By: Relevance
“…In addition to the central force, the two-range Gaussian spin-orbit term of the G3RS force [35,36] with he strengths u I = −u II = 3000 MeV is supplemented. This set of interaction parameters describes well properties of the ground and excited states of 10 Be and 12 C in the AMD+VAP calculations [37][38][39].…”
Section: A Effective Interactionsmentioning
confidence: 63%
“…In addition to the central force, the two-range Gaussian spin-orbit term of the G3RS force [35,36] with he strengths u I = −u II = 3000 MeV is supplemented. This set of interaction parameters describes well properties of the ground and excited states of 10 Be and 12 C in the AMD+VAP calculations [37][38][39].…”
Section: A Effective Interactionsmentioning
confidence: 63%
“…The most interesting and frequently investigated of these systems are approximated by a three-body structure. Extensions to excited three-body continuum states are now being pursued and attracting a lot of attention [8][9][10][11][12]. To get accurate three-body wave functions the Faddeev decomposition with different Jacobi coordinates is employed in coordinate space computations [13].…”
mentioning
confidence: 99%
“…Another interesting problem is the stability of the linear chain 3α structure in C isotopes. According to AMD and FMD calculations [12,13,26], it was suggested that the straight-line linear chain structure is not stable in 12 C but only a chain-like open triangle 3α configuration may appear in the higher 0 + state (the 0 + 3 state in the present calculation), a few MeV above the 0 + 2 state. This suggestion is supported by the recent experimental observation of 0 + states around excitation energy of 10 MeV by Itoh et al [23].…”
Section: Inpc 2013mentioning
confidence: 60%
“…However, in the case of neutron-rich Be, two α clusters develop further and level inversion occurs. Indeed, in the AMD results of Be isotopes, the breaking of the neutron magic number N = 8 is proposed also in 12 Be and 13 Be because of the lowering of the σ orbital in the cluster states as well as 11 Be. The results were consistent with a recent experimental observation of a low-lying abnormal parity state, the 1/2 − , in 13 Be reported by Kondo et al [33].…”
Section: Inpc 2013mentioning
confidence: 99%
See 1 more Smart Citation